Anthropometric profile of elite Greek female water polo players - Platanou, T.; Varamenti, E.; Soultanakis, H. (12th Annual Congress of the European College of Sport Science, Jyväskylä, Finland - July 11-14th 2007, 2007)
The physical and physiological characteristics of elite players, offer some knowledge for the minimal requirements of competitive game and the adjustments that occur during training and are important for success in many sports. As far as water polo is concerned studies have focused on male players. Thus, there is limited information of these characteristics in women. The purpose of this study is to record and assess the anthropometric characteristics and body composition of female elite water polo players. Additionally, this study wants to determine which of the above characteristics makes senior female national team water polo players (silver metal in Athens Olympic Games) differ from that of junior female national team water polo players. Twenty six female water polo players of the Greek national teams were measured. Thirteen belonged to the senior team, with 10±3 years of training experience in the 26±4 age group and thirteen belonged to the junior team 6±2 years of training experience in the 17±1 age group. Measurements dealt with anthropometric characteristics and included, body weight and height, lengths and circumferences of body proportions, diameters, skinfolds and body composition calculation. The percent of body fat was estimated based on Heuward (2002) equations by taking into consideration four skinfolds. Body composition was determined with the Health and Carter (1990) method and the anthropometric parameters were collected in accordance to the guidelines of Ross and Marfell-Jones (1996). A Ttest for independent samples was used to compare the differences between the two teams in the collected anthropometric variables, in the statistical level of significance of p<0.05. The results of this study showed that senior female water polo players didn`t differ in basic anthropometric variables when compared to the junior female players but only in limited variables, i.e. the senior players had 3 greater diameters (the bi-epicondylar femur, the biacromial and the biothoracic) and 2 circumferences (flexed bicep, relaxed gastrocnemious). The average height, body mass and lean body mass of the 26 players was 171.3±5.9 cm, 66.0±8.7 Kg and 50.4±5.8 Kg, respectively. Their body fat was 15.3±6.7 Kg and their percent body fat 22.6±6.1%. In conclusion, body type of elite female water polo players is characterized by endo-mesomorphy, with a high element of endomorphy due to the high percentage of body fat and differs from that of elite male water polo players who have less percent body fat and appear to have a balanced mesoporphy. The difference in the level of competitiveness of female water polo players between the senior national team and the junior national team does not appear to be depended on the differences of physical characteristics. There are possibly differences in the physiological or technical characteristics due to the higher intensity and specificity of training as the observed difference of flexed bicep circumference in our study.